Analisis Problematika dan Evaluasi Pelaksanaan Kurikulum dalam Pembelajaran Matematika di SMPS Deli Murni Bandar Baru - Sihombing, Artha Hadia; Sitepu, Ribka Zelin Margaretha; Panggabean, Ellis Mardiana; Situmorang, Adi Suarman (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This study aims to analyse the problems and evaluate the implementation of the curriculum in mathematics learning at Deli Murni Bandar Baru Junior High School. The research used a qualitative descriptive approach with mathematics teachers and related parties at the school as the research subjects. Data were collected through in-depth interviews, observation of the learning process in the classroom, and analysis of curriculum documents and teaching tools, such as teaching modules and assessment instruments. The data obtained were analysed using qualitative analysis techniques through the stages of data reduction, data presentation, and conclusion drawing. The results showed that the implementation of the curriculum was quite good in terms of planning, as demonstrated by the teachers' ability to develop teaching tools in accordance with the curriculum requirements. However, the implementation of learning and evaluation was not yet optimal. Teachers still tended to use conventional learning methods and had difficulty in implementing authentic assessment. These findings emphasised the need to improve teacher competence through continuous training so that the implementation of the curriculum could be carried out more effectively and have an impact on improving the quality of mathematics learning